Analisis Morfologi Pada Bahasa Mandar Dalam Ruang Lingkup Keluarga Di Desa Tanjung Lalak Kecamatan Pulau Laut Kepulauan Kabupaten Kotabaru - Husni Mubarak; Normasunah Normasunah (STKIP Paris Barantai, 2018)
AbstractThis study aims to describe the process of Mandar language affixation within the scope of the Family in the Village of Tanjung Lalak Kecamatan Pulau Laut Pulau Kotabaru Regency and describes the use of reduplication of Mandar language within the scope of Family in the Village of Tanjung Lalak Kecamatan Pulau Laut Pulau Kotabaru Regency. This research uses descriptive qualitative research method. Based on the result of the research, it can be concluded that (1) The affixation process in Mandar language includes the process of giving prefix, prefix, and confixing (prefix and ending). In the Mandar language of Tanjung Lalak village, Pulau Laut sub-district of Kotabaru regency, there are prefixes, ma-, si-, ti-, di-, pa-, ka-, pe-, and to-. Suffix (suffix) in Mandar language there are four suffixes, namely suffix -i, suffix -o, suffix -mu and suffix -ang. As for the confix (prefix and suffix) in Mandar language there are six conflicts of conflicts, conflicts, conflicts, conflicts, conflicts of pa-i, and sa-na cones. (2) The use of reduplication in Mandar languages has two, namely reduplication entirely, and partial reduplication.Keyword: Mandar language, prefix, and confixing, reduplication.